Analysis of Geographic Literacy Values in Serat Centhini as a Source of Contextual Learning in Elementary Schools - Pratiwi, Mey; Rachmadyanti, Putri; Puspita, Ari Metalin Ika (Journal of Innovation and Research in Primary Education, 2025)
Geographic literacy development in elementary education remains inadequate globally, with students struggling to connect spatial concepts to lived experiences. This study examines Serat Centhini, a classical Javanese manuscript, as a culturally embedded resource for developing geographical literacy in elementary schools. A descriptive qualitative research design was employed at Urangagung Elementary School involving 32 fifth-grade students, two teachers, and the principal. Data collection comprised textual analysis of Serat Centhini, classroom observations over eight sessions, and semi-structured interviews. Thematic analysis through data reduction, display, and conclusion drawing identified geographical literacy values, validated through source triangulation and peer debriefing. Five interconnected geographical literacy values emerged: spatial representation and orientation (87.5% student success rate), human-environment interactions (81.3% comparative analysis success), cultural-geographical interconnections (84.4% understanding achievement), historical-temporal spatial awareness (71.9% recognition of spatial changes), and moral-ecological values (90.6% enhanced environmental awareness). Implementation strategies including spatial narratives, local environmental analysis, collaborative learning, and reflective writing effectively enhanced students' spatial thinking and ecological consciousness. Findings demonstrate that classical cultural texts contain sophisticated geographical knowledge systems aligned with contemporary spatial thinking frameworks. This research contributes to place-based education theory by illustrating how culturally embedded narratives simultaneously advance spatial literacy, cultural preservation, and character development, supporting transformative education for sustainable development.